Bacterial Content in Runoff from Simulated Rainfall Applied to Plots Amended with Poultry Litter - Metcalf, J.H.; Jr, P.A. Moore; Donoghue, A.M.; Arsi, K.; Woo-Ming, A.; Blore, P.J.; Hanning, I.; Ricke, S.C.; Donoghue , D.J. (International Journal of Poultry Science, 2014)
To evaluate potential bacterial runoff from poultry litter, litter was applied to test plots and exposed to simulated rainfall 1, 8 or 15 d after litter application. Runoff samples were tested for Salmonella and Campylobacter, two bacterial pathogens commonly associated with poultry, as well as common fecal indicators such as coliforms, enterococci and Escherichia coli. The runoff samples were evaluated from treatments of no litter (control), or the equivalent of 1, 2 or 4 ton/acre of untreated poultry litter. Additionally, runoff samples from treatments of 2 tons/acre of alum-treated litter, 2 tons/acre composted litter and 2 ton/acre deep-stacked litter were compared for bacterial content. Three replicates of the treatments were performed, for a total of 21 test plots. No Campylobacter was isolated from any of the samples and the majority of samples tested negative for Salmonella. Although Salmonella was detected in runoff from many of the plots, it may have originated from sources other than the applied litter (rodents, birds, etc.) since it was detected in two of the unfertilized control plots.